A comprehensive review of the published assays for the quantitation of the immunosuppressant drug mycophenolic acid and its glucuronidated metabolites in biological fluids. (17th February 2016) - Syed, Muzeeb; Srinivas, Nuggehally R.
Abstract: Therapeutic use of mycophenolic acid (MPA) is steadily on the rise in combination with other immunosuppressant drugs in transplantation patients. The biotransformation of MPA resulted in the formation of glucuronide metabolites, MPAG and AcMPAG. There are a plethora of assays validated for the analysis of MPA alone or with MPAG/AcMPAG in various biological specimens including plasma/serum, urine, ultrafiltrate, saliva, PBMC, dried blood spots, tissue extract, tumor biopsies and vitreous humor. Based on the need for experimental work, a proper choice of the assay and internal standard may be made using the choices in the literature. While the chemical methods involving high‐performance liquid chromatography (HPLC) or LC coupled with triple quadrupole mass spectrometry (LC‐MS/MS) are popular, enzymatic assays, in spite of their higher bias, have been used for the routine drug monitoring of MPA. The objectives of the present review are: (a) to provide a focused systematic compilation of the HPLC or LC‐MS/MS methods for MPA, MPAG and/or AcMPAG published in the last decade (2005 to current) to enable visual comparison of the methods; (b) to compare and contrast a few enzymatic assays with those of the chemical methods; and (c) to discuss relevant issues/limitations and perspectives on select assays under various subheadings. Copyright © 2016 John Wiley & Sons, Ltd.